Income thresholds in the remittances-growth association? a case study of Fiji. Issue 19 (11th November 2022) - Kumar, Nikeel Nishkar; Patel, Arvind
ABSTRACT: Research indicates that remittances have mixed effects on growth. In this study, we investigate the role of income thresholds in this association for Fiji. Income thresholds are measured by thresholds in per-worker real GDP and are identified using the self-exciting threshold autoregression model over the period 1980 to 2017. A threshold autoregressive distributed lag model is subsequently developed. A single threshold in per-worker real GDP is estimated at US5891. Remittances promote growth if income exceeds the threshold but is negative otherwise. Hence, remittances support growth-enhancing activities at high-income levels but may finance imports at the expense of domestic production at lower income levels.